2021
DOI: 10.3390/molecules26216336
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Triticum aestivum Sprouts Suppresses Acetaminophen-Induced Hepatotoxicity in Mice by Inhibiting Oxidative Stress

Abstract: Wheat (Triticum aestivum L.) is the oldest known food crop, and many studies have reported that wheat shoots (i.e., wheatgrass) possess anti-cancer, anti-inflammatory, and antioxidant activities. However, the potentially ameliorative effect of wheat shoots on hepatotoxicity caused by high doses of N-acetyl-para-aminophenol (acetaminophen, APAP) has yet to be reported. C57BL/6 mice received daily oral TAE (100 or 200 mg/kg), positive control (silymarin 100 mg/kg), or negative control (saline vehicle) treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Numerous studies have shown that oxidative stress occupied prominent values in the pathogenesis of hepatotoxicity ( Guo et al, 2019 ; Lv et al, 2020 ; Temel et al, 2020 ; Jung et al, 2021 ; Lim et al, 2021 ). When the body’s oxidation and anti-oxidation are out of balance, excess reactive oxygen species will be produced, resulting in a state of oxidative stress, lipid peroxidation of cell membranes, and abnormal organelle function ( Bao et al, 2010 ; Glade and Meguid, 2017 ; Hussein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that oxidative stress occupied prominent values in the pathogenesis of hepatotoxicity ( Guo et al, 2019 ; Lv et al, 2020 ; Temel et al, 2020 ; Jung et al, 2021 ; Lim et al, 2021 ). When the body’s oxidation and anti-oxidation are out of balance, excess reactive oxygen species will be produced, resulting in a state of oxidative stress, lipid peroxidation of cell membranes, and abnormal organelle function ( Bao et al, 2010 ; Glade and Meguid, 2017 ; Hussein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver diseases have become a major global public health problem, and severe liver injury can overwhelm the self-regenerative capacity of the liver and can prove fatal [ 1 ]. Excessive oxidative stress plays a role in the pathogenesis of hepatic diseases such as alcohol-related liver disease, non-alcoholic fatty liver disease, hepatitis, fibrosis, and cirrhosis and can be induced by intrinsic factors and/or multiple xenobiotics such as alcohol and toxic compounds [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Living organisms produce reactive oxygen species (ROS) and reactive nitrogen species (RNS) via normal cellular metabolism [ 5 ]. Under normal healthy conditions, ROS and RNS generated by various pro-oxidants including alcohol [ 6 ], acetaminophen [ 2 , 4 ], ethyl carbamate [ 3 ], and fatty acids [ 7 ] are scavenged by various cellular enzymatic and non-enzymatic antioxidants, such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), glutathione (GSH), and thioredoxin. These cellular antioxidants possibly play an important role in the prevention of oxidative stress-related diseases, such as liver disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hepatoprotective and anti-inflammatory effects of ethanolic T.A. sprout extract were studied by Lim et al [ 113 ]. γ-Aminobutyric acid and α-linolenic acid contents were characterized at 209.23 and 170.92 µg/mg extract.…”
Section: Resultsmentioning
confidence: 99%